Microstructure Evolution and Phase Transformation of Ti‐1.0 wt%Fe Alloy with an Equiaxed α + β Initial Microstructure during High‐Pressure Torsion and Subsequent Annealing. Issue 9 (2nd August 2019) - Chong, Yan; Deng, Guanyu; Shibata, Akinobu; Tsuji, Nobuhiro
Abstract : Herein, the microstructure evolution and phase transformation during high‐pressure torsion (HPT) and subsequent annealing of Ti‐1.0 wt%Fe alloy with an equiaxed α + β initial microstructure are investigated. Both α and β grains in the initial microstructure fragment into smaller and elongated areas during HPT. X‐ray diffraction (XRD) analysis reveals that the deformation‐induced α to ω and β to ω phase transformations occur from the onset of HPT deformation. The β phase totally disappears after 1.5 rotations, whereas some α phase still remains even after 4 rotations. The nano‐hardness of β grains is much larger than that of α grains in the initial microstructure, due to the nano‐sized athermal ω precipitates inside the β grains. With an increase in the HPT rotation, the nano‐hardness of prior α areas continuously increases, whereas that of the prior β areas gradually decreases. During the subsequent annealing of HPT‐deformed sample, both ω to α and ω to β reverse‐phase transformations occur, and the deformation‐induced ω phase totally disappears at annealing temperatures above 400 °C. The recrystallization of α phase completes at an annealing temperature of 500 °C. At higher annealing temperatures, secondary α precipitates with ultrafine grain sizes start to appear inside the prior β areas. Abstract : The microstructure evolution and phase‐transformation behaviors of the Ti‐1.0 wt%Fe alloy with an equiaxed α + β initial microstructure during the high‐pressure torsion and subsequent annealing processes are systematically investigated in this study for the first time. The corresponding mechanical properties, including the nano‐hardness and tensile properties, are also briefly evaluated at room temperature.